Conceptual validation of the nursing diagnosis impaired verbal communication - Favretto, Débora Oliveira; Carvalho, Emilia Campos de (Online Brazilian Journal of Nursing, 2008)
This study aimed to carry out the conceptual validation of the elements of the diagnosis Impaired Verbal Communication and assess its inclusion in the taxonomy. The Concept Analysis step of Hoskins’ Validation Model was used, based on a bibliographic survey with the following descriptors: communication, nursing diagnosis, communication barriers, nursing and patient. The abstracts of 125 articles were identified, 29 of which attended to the inclusion criteria. These were analyzed to identify the defining characteristics for the diagnosis under study. It was observed that the title is limited in relation to the definition and the defining characteristics, which involve different types of communication. All characteristics presented in NANDA were found in literature; four others were also identified. The insertion of the diagnosis in domain 5 and class 5 is pertinent, although the human communication process is more comprehensive than what is previewed in this class.